THE CONCEPT AND FORMS OF EXPLOITATION IN THE NOVELS OF MULK RAJ ANAND AND ANNA BHAU SATHE - Dr. Ambadas Dadasaheb Sakat (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Mulk Raj Anand and Anna Bhau Sathe are the prominent writers of Modern Indian Literature in English and Marathi. The present paper deals with different forms of exploitation in the novels of Mulk Raj Anand and Anna Bhau Sathe with special reference to novels such as Coolie, Fakira, Untouchable, Chandan etc. Both the writers are mainly concern with the theme of exploitation. They attack on the tyranny and exploitation of working-class people in Punjab and Maharashtra. The capitalists are socially, economically and culturally sound. Such capitalists make exploitation of innocent people of the downtrodden community. In Mulik Raj Anand’s Untouchable, upper class people don’t allow the lower class people to finch water on the common well. Moreover, they are not allowed to enter into the temple. Such poor people of the lower class communities were supposed to do works of cleaning latrines in the villages. They look after the pet animals of the rich people. Young boys from the downtrodden communities work as a sweeper boy, a shoe polish boy, a chimney sweeper in big cities. They had no proper place at all in the aristocratic society. Anand and Annabhau emphasized democratic views of Karl Marx, Mahatma Gandhi, and Dr. Babasaheb Ambedkar etc.